Efficacy of avermectins against gastrointestinal nematodes of dairy cattle in temperate region ofUttarakhand - RAM, HIRA; SINGH, K; MEENA, H R; SHARMA, A K; RASOOL, T J (The Indian Journal of Animal Sciences, 2011)
A trial using avermectins (ivermectin and doramectin) was conducted in crossbred cattle maintained at high altitude (> 7500 feet above MSL). Animals positive for gastrointestinal nematode infection (n=24) based on fecal egg counts were randomly divided into groups A, Band C of 8 animals each. Ivermectin and doramectin injection were given in all animals of group A and B, respectively, through subcutaneous route at the recommended dose while the animals of group C were kept as untreated control. Efficacy ofthe drugs was calculated on 14th day post treatment by fecal egg count reduction test (FECRT). Both ivermectin and doramectin were 100% effective against commonly occurring GI nematodes of cattle.Â